THE OBJECTIVE LIMITS OF THE JUDICIAL CONTROLS OF THE UNCONSTITUCIONAL OMISSION - Gaspardo, Murilo [UNESP]; Polycarpo, Guilherme Bollini (Escola Magistratura Rio Grande Norte, 2015)
The intention on the present paper is to perform a research about the unconstitutional normative omission under the face of the rules contained on the Federal Constitution enacted in 1988. This subject shows its relevance against the open nature of the Constitution and the numerous rules which need infraconstitutional regulamentation in order to produce the effects desired by the Constituent Power. Therefore, what is intended is to show which rules need integration through legislative and administrative providences. This will be important to learn about the limits of unconstitutional omission control.
Keywords: Federal Constitution; Unconstitutional omission; Constitutionality control